Prevalence and factors associated with prediabetes among postpartum gestational diabetes mellitus mothers in Besut, Terengganu, 2018-2019 - Khamis, Mohd Fadhli (Pusat Pengajian Sains Kesihatan, Pusat Pengajian Sains Perubatan, 2017)
Age estimation is useful for human identification 1 and in determining legal age for criminal responsibility.2.Both applications are related to local legal requirements and can be applied to ageing both human remains and living people.